Dominant Rio1 kinase/ATPase catalytic mutant induces trapping of late pre-40S biogenesis factors in 80S-like ribosomes - Ferreira-Cerca, Sébastien; Kiburu, Irene; Thomson, Emma; LaRonde, Nicole; Hurt, Ed (Nucleic acids research, 2014)
Abstract. During eukaryotic ribosome biogenesis, membersof the conserved atypical serine/threonine proteinkinase family, the RIO kinases (Rio1, Rio2 andRio3) function in small ribosomal subunit biogene-sis.
Gesehen am 25.09.2020